Sound Change of Batahan Language as Malay Dialect in Mandailing Natal Regency - Muhammad Afdhaluz Zikri Lubis; Tasnim Lubis (TALENTA Publisher, 2024)
This research deals with comparative historical linguistic studies that discuss the types of sound changes from Proto-Austronesian into Batahan Malay. This research uses qualitative methods with listening and recording techniques. Data sources were obtained from informants who are native speakers of Batahan Coastal Malay. Vocabulary taken from the speakers' recordings are those listed in the swadesh list. In the sound changes of the Austronesian language into Batahan Coastal Malay based on sound position, there are only six changes out of seven changes namely metathesis, apheresis, syncope, apocope, prothesis, and paragogue.